MiR-29c/PRKCI Regulates Axonal Growth of Dorsal Root Ganglia Neurons Under Hyperglycemia - Jia, Longfei (Mol Neurobiol, 2017)
Diabetes initially induces distal axonal damage of peripheral nerves, but molecular mechanisms that mediate axonal injury are not fully understood. MircoRNAs (miRNAs) regulate axonal growth. We found that diabetic db/db mice exhibited substantial upregulation of miR-29c in dorsal root ganglia (DRG) neurons, sciatic nerve, and foot pad tissues. Bioinformatic analysis revealed PRKCI, a gene that encodes a member of the protein kinase C (PKC) iota, as a putative target for miR-29c. Western blot analysis showed that diabetic mice exhibited a considerable reduction of PRKCI protein levels in sciatic nerve tissues and DRG neurons. Using dual-luciferase assay, we found that co-transfection of a plasmid containing miR-29c binding site at 3′ UTR of PRKCI gene and miR-29c mimics effectively reduced luminescence activity, which was abolished when miR-29c seed sequences at 3′ UTR of PRKCI gene were mutated. In vitro, high glucose substantially upregulated and reduced miR-29c and PRKCI protein levels, respectively, in DRG neurons, which were associated with significant reduction of axonal growth. Knockdown of endogenous miR-29c in DRG neurons by siRNAs overcame reduced PRKCI protein and axonal growth under high glucose condition. Moreover, knockdown of PRKCI in DRG neurons by siRNAs under regular glucose condition considerably inhibited axonal growth. Together, these findings suggest that miR-29c is a negative regulator of axonal growth of DRG neurons by targeting PRKCI under hyperglycemia.